Shortening of the Induction Period of Allergic Asthma in Cynomolgus Monkeys by Ascaris suum and House Dust Mite - Katsumasa Iwashita; Hirokazu Kawasaki; Masatsugu Sawada; Mika In; Youichi Mataki; Takashi Kuwabara (Elsevier, 2008)
The development of non-human primate models of asthma requires a period of time (e.g., 0.5 -1 year). To develop the models in a short period, male cynomolgus monkeys were sensitized with dinitrophenyl-Ascaris suum (DNP-As) allergen by intraperitoneal and intramuscular injection and by intratracheal inhalation. All sensitized animals developed positive intradermal skin reaction to DNP-As. Sensitization elevated allergen-specific IgE levels in serum, the number of CCR4-positive T helper lymphocytes in peripheral blood, and IL-4 and IL-5 releases from phorbol 12-myristate 13-acetate- and ionomycin-stimulated peripheral blood. In addition, allergen challenge induced increases in lung resistance, airway inflammation, and hyperresponsiveness to inhaled methacholine. Next, animals were sensitized with house dust mite extracts (HDM) under the similar procedure. In these animals sensitized with DNP-As or HDM, inhaled fluticasone propionate and oral prednisolone inhibited the allergen-induced airway hyperresponsiveness. Taken together, monkey asthma models were successfully developed by sensitization with DNP-As or HDM under a short-term protocol (within 7 weeks). These models should be useful for the evaluation of anti-inflammatory drugs for asthma treatment. Keywords:: airway hyperresponsiveness, bronchoalveolar lavage, CCR4-positive cell, cytokine, methacholine